TSH Suppression Induces Anxiety- and Depression-like Behaviors in Rats, With Hippocampal 5-HT Loss, Notch Activation, and a Neurogenesis-Apoptosis Imbalance - Zhao, Yikun; Jiang, Honglin; Shang, Huiyuan; Xia, Zhongyuan (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: TSH suppression is widely used in thyroid cancer management; however, its neurobehavioral consequences are not well understood. Objectives: To evaluate the impact of TSH suppression on emotion-related behaviors, thyroid axis hormones, hippocampal serotonin (5-HT) levels, neurogenesis, Notch signaling, and apoptosis in a rat model. Materials and Methods: Rats were assigned to three groups: blank control, TSH replacement, and TSH suppression. TSH suppression was induced using total thyroidectomy combined with graded L-T4. Behavioral assessments were performed using open field and tail suspension tests. We measured serum levels of FT3, FT4, and TSH via ELISA, while hippocampal 5-HT levels were also quantified. Neural stem-cell proliferation and differentiation were assessed with BrdU, Nestin, NeuN, and GFAP immunohistochemistry. Notch signaling and apoptosis markers were analyzed using qPCR and Western blot techniques. Results: Compared with control and replacement groups, TSH suppression led to anxiety- and depression-like behaviors, demonstrated by greater immobility, longer rest periods, and delayed entry into the center of the open field. Additionally, we observed elevated FT3 and FT4 levels with reduced TSH, decreased levels of hippocampal 5-HT, and significant upregulation of Notch signaling pathway markers. Neurogenesis was disrupted, characterized by enhanced stem-cell proliferation but decreased neuronal differentiation, coupled with an increase in astrocyte differentiation. Furthermore, the Bax/Bcl-2 ratio increased, indicating a pro-apoptotic environment. Conclusion: The findings indicate that TSH suppression is linked to adverse mood-related behaviors, 5-HT depletion, Notch pathway activation, and an imbalance in neurogenesis and apoptosis. These results suggest that excessive suppression of the thyroid hormone axis may carry neuropsychiatric risks that need to be carefully balanced against the oncological benefits during thyroid cancer treatment.
Keywords: 5-HT; Bax/Bcl-2; Neurogenesis; Notch; Open field; Tail suspension; TSH suppression